The association of shock index and haemoglobin variation with postpartum haemorrhage after vaginal delivery: a prospective cohort pilot study. (February 2021) - Drew, T.; Carvalho, J.C.A.; Subramanian, C.; Yoon, E.W.; Downey, K.; Thorneloe, B.; Balki, M.
Highlights: Early detection of postpartum haemorrhage (PPH) reduces morbidity and mortality. Shock index and non-invasive haemoglobin (SpHb) are useful tools to detect PPH. Trends of both shock index and SpHb are associated with the amount of PPH. Shock index is a sensitive and early indicator of PPH. A negative trend in SpHb is a late sign of PPH. Abstract: Introduction: Shock index and continuous non-invasive haemoglobin monitoring (SpHb) have both been proposed for the timely recognition of postpartum haemorrhage (PPH). We sought to determine, in parallel, the association of each of shock index and SpHb with blood loss after vaginal delivery. Methods: Sixty-six women were recruited to this prospective observational study. Shock index and SpHb were recorded postpartum for 120 min. The association between each of shock index and SpHb with quantitative blood loss (QBL) at 30, 60 and 120 min postpartum was determined using linear mixed models. Area-under-the-receiver-operator-characteristic (AUROC) curves were constructed to evaluate the diagnostic ability of shock index and SpHb to detect PPH (defined as QBL ≥1000 mL). Results: Shock index trend was associated with QBL over the first 30 min ( r =0.37, P =0.002), but not over 60 or 120 min. There was an association of SpHb trend with QBL over the first 30 min ( P =0.06), but not over 60 min ( r =−0.32, P =0.009) or 120 min ( r =−0.26, P =0.03). Maximum shock index within 60 min correlated with QBL ( r =0.54, P <0.001) and was a predictor of PPH ( P =0.0012, AUROC 0.796). Maximum change in SpHb within 60 min negatively correlated with QBL ( r =−0.4, P <0.001) and was a predictor of PPH ( P =0.048, AUROC 0.761). Conclusions: The trend of shock index and its peak values are associated with blood loss after vaginal delivery and are early indicators of PPH. Negative trend of SpHb is a late sign of PPH and has a weaker association with blood loss than shock index.